Defined Pig Microbiota with a Potential Protective Effect against Infection with Salmonella Typhimurium - Horvathova, Kristyna; Modrackova, Nikol; Splichal, Igor; Splichalova, Alla; Amin, Ahmad; Ingribelli, Eugenio; Killer, Jiri; Doskocil, Ivo; Pechar, Radko; Kodesova, Tereza; Vlkova, Eva (Microorganisms, 2023)
A balanced microbiota is a main prerequisite for the host's health. The aim of the present work was to develop defined pig microbiota (DPM) with the potential ability to protect piglets against infection with Salmonella Typhimurium, which causes enterocolitis. A total of 284 bacterial strains were isolated from the colon and fecal samples of wild and domestic pigs or piglets using selective and nonselective cultivation media. Isolates belonging to 47 species from 11 different genera were identified by MALDI-TOF mass spectrometry (MALDI-TOF MS). The bacterial strains for the DPM were selected for anti-Salmonella activity, ability to aggregate, adherence to epithelial cells, and to be bile and acid tolerant. The selected combination of 9 strains was identified by sequencing of the 16S rRNA gene as Bacillus sp., Bifidobacterium animalis subsp. lactis, B. porcinum, Clostridium sporogenes, Lactobacillus amylovorus, L. paracasei subsp. tolerans, Limosilactobacillus reuteri subsp. suis, and Limosilactobacillus reuteri (two strains) did not show mutual inhibition, and the mixture was stable under freezing for at least 6 months. Moreover, strains were classified as safe without pathogenic phenotype and resistance to antibiotics. Future experiments with Salmonella-infected piglets are needed to test the protective effect of the developed DPM.
Keywords: probiotic properties testing; gnotobiotic piglets; intestinal pathogens; bacterial consortium; pig intestinal bacteria